Pregnancy after hydrosalpinx treatment with Essure. (26th March 2013) - Inocêncio, Gonçalo; Coutinho, Lúcia; Maciel, Raquel; Barreiro, Márcia
Abstract : We present a case of a 29-year-old woman, with a history of ectopic pregnancy, which required left salpingectomy, and with a tortuous and impermeable right fallopian tube, compatible with hydrosalpinx. As hydrosalpinx itself can compromise a future pregnancy, treatment with Essure was proposed before passing to medically assisted procreation techniques. Five months after placement of Essure in the right fallopian tube, an in vitro fertilisation cycle was successfully completed and the woman had a singleton pregnancy and vaginal delivery without intercurrences.